2012
DOI: 10.1016/j.pt.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

PfCRT and its role in antimalarial drug resistance

Abstract: Plasmodium falciparum resistance to chloroquine, the former gold standard antimalarial drug, is mediated primarily by mutant forms of the ‘Chloroquine Resistance Transporter’ (PfCRT). These mutations impart upon PfCRT the ability to efflux chloroquine from the intracellular digestive vacuole, the site of drug action. Recent studies reveal that PfCRT variants can also affect parasite fitness, protect immature gametocytes against chloroquine action, and alter P. falciparum susceptibility to current first-line th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
289
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(300 citation statements)
references
References 127 publications
(167 reference statements)
9
289
0
2
Order By: Relevance
“…To date, several studies have demonstrated the association between resistance or decrease susceptibility to 4-amino-quinoline resistance and mutation in crt gene, changes in expression profiles and/or copy number variation in mdr1 gene ( Borges et al , 2011; Duraisingh & Cowman, 2005; Holmgren et al , 2006). Single nucleotide polymorphism (SNP) in Pfcrt (codon 76) is associated with CQ and AQ resistance in P. falciparum ( Ecker et al , 2012; Fidock et al , 2000; Ochong et al , 2003). Recent studies also identified potential crt background mutations; Ile356Thr and Asn326Ser that associate with artemisinin resistance ( Miotto et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several studies have demonstrated the association between resistance or decrease susceptibility to 4-amino-quinoline resistance and mutation in crt gene, changes in expression profiles and/or copy number variation in mdr1 gene ( Borges et al , 2011; Duraisingh & Cowman, 2005; Holmgren et al , 2006). Single nucleotide polymorphism (SNP) in Pfcrt (codon 76) is associated with CQ and AQ resistance in P. falciparum ( Ecker et al , 2012; Fidock et al , 2000; Ochong et al , 2003). Recent studies also identified potential crt background mutations; Ile356Thr and Asn326Ser that associate with artemisinin resistance ( Miotto et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Mutation at positions 86, 184, 1034, 1042, and 1246 in Pfmdr1 mediate and/or modulate CQ, LM and mefloquine resistance ( Ecker et al , 2012; Price et al , 1999; Price et al , 2004; Sisowath et al , 2005). Studies in the rodent malaria Plasmodium chabaudi found no association between crt and CQ resistance ( Afonso et al , 2006; Hunt et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of the 1,2,4-oxadiazole series mirrored that of chloroquine rather than that of the DHFR inhibitors pyrimethamine and cycloguanil, with a 60-fold or greater increase in activity against pfcrt wild-type strain HL1212 than pfcrt mutant HL1210 (Table 3). These results suggest that mutated PfCRT might play a direct role in P. falciparum resistance to the 1,2,4-oxadiazole series and, by extension, that the mode of action of these compounds could reside in the digestive vacuole, from which mutant forms of the PfCRT transmembrane transporter are postulated to exclude chloroquine in resistant parasites (32,33).…”
Section: Genotypic Validation Of Selected P Falciparum Strainsmentioning
confidence: 90%
“…In the case of AQ/SP, mediators of drug resistance are well characterized. For AQ, resistance is mediated principally by the 76T mutation in Plasmodium falciparum crt (pfcrt) (16)(17)(18), which encodes a putative drug transporter, and is augmented by polymorphisms in a second predicted transporter gene, pfmdr1. The pfmdr1 86Y and 1246Y mutations are common in Africa and mediate decreased sensitivity to AQ (16,(19)(20)(21); the Y184F allele is also highly polymorphic but is of uncertain significance.…”
mentioning
confidence: 99%